An Sosialisasi Strategi Pemasaran Digital Pasca Panen Hidroponik Bagi Siswa Ekstrakulikuler Green Be di SMAN 1 Pemali - Rumalessin, Ummu Artha Tsary; Ali, Hendrik; Vera, Lusi Olis; Alamsyah, Redi; Pratama, Muhammad Setya; Gucchi, Anjaka Ray; Annafi, Ganif Nur (Politeknik Negeri Batam, 2025)
The agricultural sector continues to experience a decline in income, largely due to a mismatch between production capacity and the empowerment of farmers in post-harvest product marketing. This issue is exacerbated by the continued reliance on traditional marketing practices, which limit farmers' access to broader consumer markets. Thus, addressing this gap is critical for enhancing farmers' bargaining power by facilitating direct connections between producers and consumers. This community initiative aimed to enhance the capacity of millennial young farmers to digitally market post-harvest hydroponic agricultural products through the TikTok e-commerce platform. The program employed educational seminars and hands-on training focused on digital marketing strategies and the utilization of e-commerce tools. The participants comprised 30 students from SMAN 1 Pemali, all members of the